Gothic Modernisms
XII, 232 p.
Keywords: This is the first full length exploration of the relationship between Gothic fiction and Modernism in fiction and film. The Gothic's fascination with images of the fragmented self is echoed in the Modernist concern with the psyche and the paranoia of the everyday. The contributors explore how the Gothic influences a range of writers including James Joyce, D.H. Lawrence, Virginia Woolf, May Sinclair, Elizabeth Bowen and Djuna Barnes.